Issues and Challenges In the Business Strategy of Hai-O Enterprise Berhad - A Case Study - Adenan, Adelina (2010)
This is a case study on Hai-O Enterprise Berhad, the leading traditional healthcare group in Malaysia that has successfully promoted traditional Chinese medicine to a corporate level.